Delayed Versus Immediate Cord Clamping in Preterm Infants. Issue 5 (May 2018) - Tarnow-Mordi, William; Morris, Jonathan; Kirby, Adrienne; Robledo, Kristy; Askie, Lisa; Brown, Rebecca; Evans, Nicholas; Finlayson, Sarah; Fogarty, Michael; Gebski, Val; Ghadge, Alpana; Hague, Wendy; et al.
Abstract : (Abstracted from N Engl J Med 2017;377:2445–2455) Systemic reviews have shown that delaying the time of umbilical cord clamping can improve outcomes of preterm newborns. One such study found enhanced placental transfusion through delayed cord clamping, cord-palpation, or a combination of the 2 practices caused a lower infection and mortality rate when compared with immediate clamping.